Yeasts and moulds species evolving during production of traditional Beaten cheese - Vesna Levkov; Natasha Gjorgovska; Sandra Mojsova (My University, 2019)
ABSTRACT The yeasts and moulds present in traditional ewe’s milk beaten cheese produced in two different farmhouses were the object of survey in this study. The changes in their number during manufacturing and ripening were followed and the isolation and determination of the isolates were also made. After serial dilution with sterile physiological solution samples of milk and cheese were cultivated on YGC agar by incubation at 25˚C for 5 days. The isolated colonies were determinate based on their morphological and physiological characteristics. The yeasts were present during the whole process of cheese production and ripening. Their number in the milk used for cheese production in first and second farmhouse were 3.71-4.38 log cfu/ml and 4.13-4.47 log cfu/ml respectively. The yeasts were most present in beaten cheese in the samples collected during the dry salting (5.04-5.47 log cfu/g) and 10 days brining (5.09-5.31 log cfu/g) in the first farmhouse and during the dry ripening (4.77-5.04 log cfu/g) in the cheese samples collected from the second farmhouse. Trichosporon pulullans, Debariomyces hansenii, Pichia polymorpha and Kluyveromyces lactis were prevailing species in traditional beaten cheese. The moulds were not continually present in examined traditional cheese indicating of its additional contamination. The highest numbers of moulds were count in cheese samples collected from curd (4.69 log cfu/g), dry ripening (3.77 log cfu/g), dry salting (4 log cfu/g) and 10 days brining (4.17 log cfu/g). The prevaling species were determinate as Aspergilus niger, Fusarium oxysporum, Alternaria tenuis, Curvularia lunata, Penicillium spinulosum.
Keywords: Key words: traditional beaten cheese, yeasts species, moulds species, dynamic of microorganisms